Análise de cenários paisagísticos, turísticos e hoteleiros do Município de Guaramiranga-CE - Freitas, Bruna Maria Rodrigues de (2018)
This research presents discussion on landscape, tourism and lodging in Guaramiranga/CE and provides application proposals towards its responsible profiting. Despite the fact the small town integrates the Environmental Protection Area in Maciço de Baturité, it presents transformations in the landscape derived from socioeconomic activities based especially in agriculture and tourism. The research’s main goal was to analyse the landscape and touristic scenery of Guaramiranga, as well as the impact on landscape. For that, theoretical and methodological perspective sustained by landscape geoecology and an interdisciplinary view were used. Those choices enabled integrated analysis of environmental, biological, social and cultural elements of the area. Data was collected through bibliographical research, field work, it was presented interviews with local leadership and people, and results from the teaching experience from the researcher. From the data collected, it was possible to verify use and occupation, the problems and landscape potentialities for touristic purpose. This way, proposals were aimed at social, environmental and touristic context, highlighting landscape and touristic routes. The analysis of landscape and touristic scenery presented the need of decentralization of touristic activity in Guaramiranga’s urban area, and a better offer of lodging services. For that, it is necessary the association among touristic development agencies for a better adjustment of local structure, as well as publicizing touristic routes, service quality, actions oriented to organize touristic activities by public policies.